2008
DOI: 10.1002/bip.20926
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and mechanism of cutinase stabilization by trehalose

Abstract: Trehalose has been widely used to stabilize cellular structures such as membranes and proteins. The effect of trehalose on the stability of the enzyme cutinase was studied. Thermal unfolding of cutinase reveals that trehalose delays thermal unfolding, thus increasing the temperature at the midpoint of unfolding by 7.2 degrees . Despite this stabilizing effect, trehalose also favors pathways that lead to irreversible denaturation. Stopped-flow kinetics of cutinase folding and unfolding was measured and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…Studies have also demonstrated that surface tension of trehalose solutions depends on trehalose concentration and there is a direct correlation between surface tension and T m [39]. The present study demonstrates a significant decrease in rcABC I flexibility in the presence of trehalose which has been reported for numerous enzymes [36,37,40,41]. Since trehalose is approved by FDA as a safe cosolvent, it can be used as a special stabilizer for cABC I stabilization and be administered in vivo in treatment of SCI.…”
Section: Circular Dichroism Studiessupporting
confidence: 48%
“…Studies have also demonstrated that surface tension of trehalose solutions depends on trehalose concentration and there is a direct correlation between surface tension and T m [39]. The present study demonstrates a significant decrease in rcABC I flexibility in the presence of trehalose which has been reported for numerous enzymes [36,37,40,41]. Since trehalose is approved by FDA as a safe cosolvent, it can be used as a special stabilizer for cABC I stabilization and be administered in vivo in treatment of SCI.…”
Section: Circular Dichroism Studiessupporting
confidence: 48%
“…Compared to its close homologue, originating from F. solani, it seems slightly more thermotolerant, as it retains 80% of its activity after 1h incubation at 30 o C, compared to 60% in the case of F. solani cutinase [28]. Improving the robustness of the latter has been the target of intensive research efforts, due to its potential as industrial biocatalyst [12,49,69] and a Z-score of 10.9 (Dali server). A structure-based sequence alignment between the two proteins did not show any conservation of the residues implicated in calcium binding.…”
Section: Effect Of Temperature and Ph On Activity Of Focut5amentioning
confidence: 98%
“…96 In case of unfolding of cutinase by heat, trehalose increases the melting temperature of the enzyme by delaying thermal unfolding of an intermediate. 97 Trehalose compensates for the altered entropy of the process by increasing the contribution of enthalpy to the process, making unfolding a thermodynamically unfavorable process. On exposure to heat, yeast produces trehalose, along with heat shock proteins, on a large scale.…”
Section: Biopreservative Action Of Trehalosementioning
confidence: 99%